The effectiveness of the TPASK-C approach practicum model in improving self-efficacy and research skills of prospective biology teachers - Djohar Maknun; Jajang Aisyul Muzakki; Ipin Aripin (Journal of Environment and Sustainability Education, 2025)
This study aims to investigate the effectiveness of implementing the Technological Pedagogical and Science Knowledge-Contextual (TPASK-C) practicum model in improving the self-efficacy and research skills of prospective biology teachers. This study employs a quasi-experimental design with a pretest-posttest control group. Research data were collected using tests and non-tests. Test data were used to collect research skills data. Self-efficacy data were collected using questionnaires. Research data were analyzed using qualitative and quantitative techniques, as well as effect-size analysis, to analyze the effectiveness of the treatment given to the tested variables. The results of the study found that the TPASK-C practicum model made a significant contribution to the formation of self-efficacy and research skills in prospective biology teacher students. The results of the t-test on the achievement of self-efficacy and research skills showed a sig. α <0.005, which indicated a significant difference between the two classes tested. Effect size testing showed Cohen's d values ​​(1.338 and 1.469), indicating that TPASK-C is effective in equipping students with self-efficacy and research skills. The results of this study are expected to be an alternative practicum model that can be widely applied in teacher training institutions (LPTK) to facilitate efforts to improve self-efficacy and research skills in prospective biology teacher students in Indonesia.